The Effect Of Transformational Leadership On Job Performance : The Moderating Role Of Organizational Citizenship Behaviour In Malaysia Service Industry - Kher, Chin Kui (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aimed to study the relationship between five dimensions of transformational leadership and job performance and the moderating role of Organizational Citizenship Behaviour (OCB). A total of 190 employees in Malaysia service industry as respondents were participated in the research questionnaire. Convergent validity, discriminant validity, reliability and hypothesis testing were tested by using SmartPLS2. This study revealed that only two dimension of transformational leadership: idealized influence (behaviour) and intellectual stimulation were positively related to the job performance. In addition, OCB only partially moderates the relationship between transformational leadership and job performance such as inspirational motivation, individualized consideration and job performance. In conclusion, there are new findings and value was added to expand the framework of transformational leadership, OCB and job performance which is useful in terms of theoretical and practical for scholars and corporates.